Pediatric Drug Induced Sleep Endoscopy: A Simple Sedation Recipe. (May 2020) - Adler, Adam C.; Musso, Mary F.; Mehta, Deepak K.; Chandrakantan, Arvind
Objective: To describe a minimalist approach to sedating children for DISE procedures. Methods: We searched existing literature and derived and tested our algorithm on patients using evidence-based studies. Results: We were able to successfully sedate, without airway intervention, 15 highly complex children with a variety of comorbidities for DISE procedures. Conclusion: We describe a minimalistic sedation approach for DISE procedures in highly complex children. Further studies are required to compare this regimen to natural sleep states.